2021
DOI: 10.1186/s12894-021-00785-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-emptive pregabalin and multimodal anesthesia on postoperative opioid requirements in patients undergoing robot-assisted laparoscopic prostatectomy

Abstract: Background Previous findings indicate that pre-emptive pregabalin as part of multimodal anesthesia reduces opioid requirements compared to conventional anesthesia in patients undergoing robot-assisted laparoscopic prostatectomy (RALP). However, recent studies show contradictory evidence suggesting that pregabalin does not reduce postoperative pain or opioid consumption after surgeries. We conducted a register-based analysis on RALP patients treated over a 5-year period to evaluate postoperative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the analgesic effect of pregabalin is controversial. 29 Therefore, the effects of each element of the NOMA protocol require verification. However, our results showed that the NOMA protocol was effective regardless of the effectiveness of each component and showed the advantage of multimodal analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analgesic effect of pregabalin is controversial. 29 Therefore, the effects of each element of the NOMA protocol require verification. However, our results showed that the NOMA protocol was effective regardless of the effectiveness of each component and showed the advantage of multimodal analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have been conducted on the preemptive administration of pregabalin for various types of surgery with variable results [8], [9], [10], [11], [12], [13]. There has been substantial debate about the benefits of preemptive pregabalin for post-operative pain, so the need for further studies to determine the benefits of preemptive pregabalin administration in certain doses on various post-operative variables is clear.…”
Section: Introductionmentioning
confidence: 99%